Antibody response to hepatitis B vaccine is independently associated with hepatitis B breakthrough infection among adults: Results from a three-year follow-up study in China. Issue 16 (12th April 2018) - Zhang, Li; Yan, Bingyu; Lv, Jingjing; Liu, Jiaye; Wu, Wenlong; Feng, Yi; Xu, Aiqiang
Abstract: Hepatitis B breakthrough infection (HBBI) and its risk factors are rarely reported among adults in China. In 2009–2010 in three townships of China, hepatitis B vaccine (HepB) administration and anti-HBs detection after HepB were conducted among the residents aged 18–59 years. HBsAg, anti-HBs and anti-HBc were detected for these vaccinees in 2013. A total of 252 out of 4701 vaccinees turned to be positive for anti-HBc in 2013, but nobody was positive for HBsAg. The HBBI rate was 5.36% (95% CI 4.73, 6.04). The highest rate was found in age-group of 18–29 years (7.33%, 95% CI : 5.31, 9.82). The rate was significantly different by the residential townships ( P  < 0.001) and by the antibody response to HepB ( P  = 0.003). Multivariate analysis showed that anti-HBs response to HepB was the independent risk factor of HBBI. The study documents the association between hyporesponse to HepB and HBBI among adults. It also suggests more attention should be given to new HBV infection among young adults.